Brow and Eyelid Rejuvenation: Trends from the 100 Most Cited Articles over 30 Years - Doga Kuruoglu; Cristina A. Salinas; Daniel S. Kirk; Chin-Ho Wong; Basel A. Sharaf (Medicina, 2023)
Background and Objective: Various periorbital rejuvenation techniques have been introduced over the last 3 decades. This study highlights important milestones in the evolution of periorbital rejuvenation surgery by identifying the 100 most-cited articles in this field. Material and Methods: The Web of Science citation index was used to identify the 100 most-cited articles concerning periorbital rejuvenation. Articles published in English from January 1989–April 2020 describing periorbital rejuvenation-related surgical techniques, facial aging, and anatomy were included. The terms “lower blepharoplasty”, “upper blepharoplasty”, “browlift”, “browplasty”, “endobrow lift”, “endoscopic brow”, “Foreheadplasty”, “lower eyelid anatomy”, “upper eyelid anatomy”, “forehead lift”, “eyelid rejuvenation”, “canthopexy”, “canthoplasty”, “eyelid fat pad”, “orbital fat pad”, “tear trough”, and “eyelid bags” were entered into the citation search. Web of Science Core Collection was the database used for the search. A manual review of the initial 159 studies was performed. Articles describing reconstructive or non-invasive techniques, injectable fillers, lasers, and neurotoxins were excluded. Of the 100 most-cited articles, the publication year, specialty journal, the corresponding author’s primary specialty, the focus of the article, the corresponding author’s country of residence, the type of study, and the level of evidence were analyzed. Results: The mean number of citations per article was 75 ± 42. There were more articles published from 1989–1999 (n = 53) than later decades. Most articles originated from the USA (n = 82) and were published in plastic surgery journals (n = 81). Plastic surgery was the primary specialty of the corresponding authors (n = 71), followed by oculoplastic surgery (n = 22). Most articles (n = 69) reported on surgical techniques. Of the clinical studies (n = 69), 45 (79%) provided level IV evidence. Conclusions: Of the 100 most-cited studies on periorbital rejuvenation, studies focusing on periorbital anatomy, aging, and surgical techniques comprised the most-cited publications. An anatomically based approach accounting for age-related changes in the periorbital structures is paramount in the field of contemporary periorbital rejuvenation.